"Kick That Population Commission in the Ass": The Nixon Administration, the Commission on Population Growth and the American Future, and the Defusing of the Population Bomb - Hoff, Derek S. (My University, 2011)
The article explores the population policies of the administration of U.S. President Richard M. Nixon, especially those espoused by the U.S. Congress' Commission on Population Growth and the American Future chaired by philanthropist and Malthusian John D. Rockefeller III. It considers the influence of the 1798 publication "Essay on Human Population," by Thomas Malthus, and the book "The Population Bomb," by Paul Ehrlich, on popular perceptions on the relationship between population growth and natural resources. Other subjects considered include U.S. Cold War policies towards population and foreign aid, American beliefs about communism and population, and laissez-faire economics.
Keywords: Richard M. Nixon; Population policy; John D. Rockefeller; Thomas Malthus; Malthusianism; United States